A polyurethane composite elastomer and a method for preparing the same

CN117264169BActive Publication Date: 2026-10-16YANSHAN UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311208812.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-09-19
Publication Date
2026-10-16
Estimated Expiration
2043-09-19

AI Technical Summary

Technical Problem

但该方案在实际生产过程中还需要考虑多官能团助剂在浇注型聚氨酯弹性体中由于反应较快,导致交联密度不均匀、加工性变差等问题

Benefits of technology

[0032] This invention mixes polyurethane prepolymer, nanofillers, and chain extenders, and uses a two-step hot-pressing method to form a polyurethane composite elastomer with the hard phase regions of the nanofillers and polyurethane serving as crosslinking points during processing through in-situ reaction. It not only possesses excellent heat resistance but also good mechanical properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117264169B_ABST
    Figure CN117264169B_ABST
Patent Text Reader

Abstract

The application discloses a polyurethane composite elastomer and a preparation method thereof. The method comprises the following steps: stirring and mixing a polyurethane prepolymer, a nano filler and a chain extender to obtain a precursor; performing one-time hot pressing and two-time hot pressing on the precursor; and annealing; wherein the temperature T1 of the one-time hot pressing is lower than the temperature T2 of the two-time hot pressing. The polyurethane composite elastomer provided by the application can realize high tensile strength, storage modulus and mechanical strength, and meets the heat resistance and dynamic performance requirements of the polyurethane elastomer in the fields of tires, dynamic sealing and shock absorption.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of polyurethane elastomer technology, and in particular to a polyurethane composite elastomer and its preparation method. Background Technology

[0002] Cast polyurethane elastomers (CPUEs) possess a wide hardness range, high strength, modulus, and elasticity, as well as resistance to wear, oil, chemical corrosion, aging, and radiation. They are widely used in defense, metallurgy, mining, electromechanical, textile, shoemaking, and automotive industries. However, CPUEs generate significant internal heat, which limits their application. Polyurethane elastomers, due to their excellent mechanical properties, high wear resistance, and ease of preparation, have extensive applications in tires and dynamic seals. However, the mechanical properties of polyurethane elastomers weaken significantly at high temperatures, thus limiting their operating temperature to generally below 120°C, further restricting their application. Cast polyurethane elastomers are obtained by casting liquid resin through a casting process and reacting to form a mold. Their heat resistance can be enhanced by increasing the degree of crosslinking of the elastomer. For example, the cast polyurethane elastomer disclosed in patent document CN 104448197A improves heat resistance by introducing trimethylolpropane to increase the degree of crosslinking. However, in actual production, this approach needs to consider issues such as uneven crosslinking density and poor processability caused by the rapid reaction of multifunctional additives in cast polyurethane elastomers. Therefore, improving the elasticity and heat resistance of cast polyurethane through modification and preparation process improvements is of great significance. Summary of the Invention

[0003] To address the aforementioned technical problems, this invention provides a high-temperature resistant polyurethane composite elastomer and its preparation method, which not only has good heat resistance but also excellent mechanical properties and strength, and can be used for a long time under high-temperature conditions.

[0004] To achieve the above objectives, the technical solution adopted by the present invention is as follows:

[0005] On one hand, the present invention provides a method for preparing a polyurethane composite elastomer, comprising the following steps:

[0006] (1) The polyurethane prepolymer was mixed with nanofillers and chain extenders to obtain the precursor;

[0007] (2) The precursor obtained in step (1) is subjected to a first hot pressing and a second hot pressing.

[0008] (3) The polyurethane composite elastomer is obtained after annealing.

[0009] The temperature T1 of the first hot pressing is lower than the temperature T2 of the second hot pressing.

[0010] In a preferred embodiment, the temperature T1 of the one-time hot pressing is 80 to 100°C, for example, 80°C, 85°C, 90°C, 95°C, 100°C or any temperature between them;

[0011] Preferably, the hot pressing time is 8-10 minutes;

[0012] Preferably, the pressure of the single hot pressing is 0.5 to 1 MPa.

[0013] In a preferred embodiment, the temperature T2 of the secondary hot pressing is 180 to 220°C, for example, 180°C, 185°C, 190°C, 195°C, 200°C, 205°C, 210°C, 215°C, 220°C or any temperature between them;

[0014] Preferably, the secondary hot pressing molding time is 10-20 minutes;

[0015] Preferably, the pressure of the secondary hot pressing is 0.5 to 1 MPa.

[0016] In a preferred embodiment, the annealing temperature is 100–120°C;

[0017] Preferably, the annealing time is 2 to 3 hours.

[0018] In a preferred embodiment, the polyurethane prepolymer is a diisocyanate-terminated polyether polyurethane prepolymer or a diisocyanate-terminated polyester polyurethane prepolymer, which is obtained by reacting polyether polyol or polyester polyol with diisocyanate.

[0019] Preferably, the polyether polyol is polytetramethylene ether diol (PTMG);

[0020] Preferably, the polyester polyol is polybutylene adipate (PBA);

[0021] Preferably, the diisocyanate is selected from at least one of toluene diisocyanate (TDI), diphenylmethane diisocyanate (MDI), and terephthalic diisocyanate (PPDI).

[0022] In a preferred embodiment, the content of terminal isocyanate groups in the polyurethane prepolymer is 5-6 wt%.

[0023] In some specific embodiments, the polyurethane prepolymer can specifically be exemplified by the TDI-PTMG, MDI-PTMG, and PPDI-PTMG type prepolymers of Zibo Yahuaxin Rubber & Plastics Co., Ltd.

[0024] In a preferred embodiment, the chain extender is dimethylthiotoluene diamine (DMTDA).

[0025] In a preferred embodiment, the nanofiller is selected from nano-silica;

[0026] Preferably, the particle size of the nanofiller is 40–60 nm;

[0027] Preferably, the mass of the nanofiller is 0.2 to 3 wt% of the mass of the polyurethane prepolymer.

[0028] In a preferred embodiment, the molar ratio of terminal isocyanate groups to chain extender in the polyurethane prepolymer is 1:0.35 to 0.45.

[0029] In some specific embodiments, step (1) involves mixing the polyurethane prepolymer with the nanofiller and the chain extender, which includes mixing the polyurethane prepolymer with the nanofiller for 20 to 30 minutes and then adding the chain extender and mixing for 6 to 10 minutes.

[0030] In another aspect, the present invention provides a polyurethane composite elastomer obtained by the above preparation method.

[0031] The above technical solution has the following advantages or beneficial effects:

[0032] This invention mixes polyurethane prepolymer, nanofillers, and chain extenders, and uses a two-step hot-pressing method to form a polyurethane composite elastomer with the hard phase regions of the nanofillers and polyurethane serving as crosslinking points during processing through in-situ reaction. It not only possesses excellent heat resistance but also good mechanical properties.

[0033] This invention prepares polyurethane composite elastomers by adding nanofillers to polyurethane prepolymers and using a two-step hot-pressing process. The secondary hot-pressing process allows for better control of the reaction rate and gelation degree, improving processing performance and optimizing the formation of microphase separation structures. This invention achieves a tensile strength of 600%, a tensile strength exceeding 40 MPa, a storage modulus exceeding 20 MPa at 135°C, and a mechanical loss tangent exceeding 0.16 at 0°C using low nanofiller content, thus better addressing the shortcomings of insufficient heat resistance and dynamic performance of polyurethane elastomers in applications such as tires, dynamic seals, and shock absorption.

[0034] In this invention, when nano-silica is used as a nanofiller, the presence of hydroxyl groups on its surface allows some of these hydroxyl groups to react with the isocyanate groups of the prepolymer, grafting polyurethane chains onto the nano-silica surface. Furthermore, unreacted hydroxyl groups on the silica surface can form hydrogen bonds with the hard segments of the polyurethane. Therefore, nano-silica not only acts as a crosslinking point in the composite elastomer but also enhances the stability of the hard phase region, thereby improving the heat resistance and mechanical properties of the polyurethane elastomer.

[0035] The polyurethane composite elastomer provided by this invention has a low content of nano-silica, a simple preparation method, and is convenient for raw material selection and formulation control, making it easy to use in industrial applications. It has potential application value in fields such as high-temperature sealing, shock absorption, and tires. Attached Figure Description

[0036] Figure 1 This is a storage modulus-temperature curve obtained by DMA testing of the polyurethane composite elastomers prepared in the comparative examples and embodiments of the present invention.

[0037] Figure 2 This is a loss modulus-temperature curve of the polyurethane composite elastomers prepared by the comparative examples and embodiments of the present invention in the DMA test.

[0038] Figure 3 This is a loss factor-temperature curve of the polyurethane composite elastomers prepared by the comparative examples and embodiments of the present invention in the DMA test.

[0039] Figure 4 This is a tensile stress-strain curve of the polyurethane composite elastomers prepared in the comparative examples and embodiments of the present invention.

[0040] Figure 5 This is an atomic force microscope (AFM) modulus image of the polyurethane composite elastomer prepared in Example 1 of this invention. Detailed Implementation

[0041] The following embodiments are merely some, not all, of the embodiments of the present invention. Therefore, the detailed descriptions of the embodiments provided below are not intended to limit the scope of the claimed invention, but merely to illustrate selected embodiments. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without inventive effort are within the scope of protection of the present invention.

[0042] In this invention, unless otherwise specified, all equipment and raw materials are commercially available or commonly used in the industry. The methods described in the following embodiments are conventional methods in the art, unless otherwise specified.

[0043] In the following examples, the TDI-PTMG prepolymer was purchased from Zibo Yahuaxin Rubber & Plastics Co., Ltd., and the content of terminal isocyanate groups was 6%. The nano-silica was purchased from Shanghai Maclean Biochemical Technology Co., Ltd., and the particle size was 50±5nm.

[0044] Example 1

[0045] The preparation method of the polyurethane composite elastomer in this embodiment includes the following steps:

[0046] (1) 6g of TDI-PTMG type prepolymer and 1wt% of nano silica by mass of prepolymer were mechanically stirred for 30min to make them evenly mixed, so as to obtain a prepolymer-nano silica blend.

[0047] (2) Add 0.73g of dimethylthiotoluene diamine (DMTDA) to the prepolymer-nano silica blend and mechanically stir at room temperature for 10min to mix it evenly to obtain the precursor;

[0048] (3) Place the precursor in a polytetrafluoroethylene plate and perform a low-temperature hot pressing operation. The temperature of the hot press is 90°C, the vacuum time is 6 min, the pressure is 0.65 MPa, and the hot pressing time is 10 min.

[0049] (4) The film obtained in step (3) is subjected to high-temperature hot pressing operation. The temperature of the hot press is 190°C, the vacuum time is 6 min, the pressure is 0.65 MPa, and the hot pressing time is 15 min.

[0050] (5) The film obtained in step (4) is vacuum annealed at 120°C for 2 hours.

[0051] Example 2

[0052] The preparation process of the polyurethane composite elastomer in this embodiment is the same as in embodiment 1, except that in step (1), the amount of nano-silica added is 1.5 wt%.

[0053] Example 3

[0054] The preparation process of the polyurethane composite elastomer in this embodiment is the same as in embodiment 1, except that in step (1), the amount of nano-silica added is 2wt%.

[0055] Example 4

[0056] The preparation process of the polyurethane composite elastomer in this embodiment is the same as that in embodiment 1, except that the amount of nano-silica added in step (1) is 2.5 wt%.

[0057] Example 5

[0058] The preparation process of the polyurethane composite elastomer in this embodiment is the same as in embodiment 1, except that in step (1), the amount of nano-silica added is 3wt%.

[0059] Comparative Example 1

[0060] The preparation process of the polyurethane composite elastomer in this embodiment is the same as that in embodiment 1, except that no nanofiller is added in step (1).

[0061] Performance testing:

[0062] The polyurethane composite elastomers prepared in Examples 1-5 and Comparative Example 1 were subjected to DMA and tensile tests, and the results are shown in the figure. Figures 1-4 .

[0063] Figure 1 The storage modulus graph illustrates the elastic behavior of the composite elastomer. As temperature increases, the storage modulus decreases, and the temperature at the inflection point of this sharp decrease is the viscous-flow transition temperature. The graph shows that compared to polyurethane elastomers without nanofillers, the addition of nano-silica improves the heat resistance of the polyurethane composite elastomer. Furthermore, the viscous-flow temperature of the polyurethane composite elastomer gradually increases with increasing nano-silica content; for example, the viscous-flow temperature of the polyurethane composite elastomer prepared in Example 4 reached 142.5℃. However, in Example 5, when the nano-silica content reached 3wt%, the viscous-flow transition was not significant, possibly because the high filler content led to agglomeration, affecting the product performance.

[0064] Figure 2 The loss modulus plot illustrates the viscous behavior of the composite elastomer, specifically the heat dissipation of the sample during deformation. From... Figure 2 As can be seen from the above, the polyurethane composite elastomer prepared in the embodiments of the present invention maintains a high loss modulus over a wide temperature range. Therefore, during mechanical motion, mechanical energy can be dissipated by converting mechanical energy into heat energy through intramolecular friction, thus exhibiting good damping characteristics.

[0065] Figure 3 The graph shows the loss factor, with the peak value representing the glass transition temperature of the sample. As can be seen from the graph, from Comparative Example 1 to Example 5, with the increase of nano-silica content, the peak temperature of the loss factor gradually shifts towards higher temperatures. This indicates that the glass transition temperature of the polyurethane composite elastomer increases, and thus the loss factor also increases.

[0066] pass Figure 1-3 In this embodiment, the nano-silica added to the composite elastomer acts as a physical crosslinking point because the hydroxyl groups on its surface can react with the isocyanate in the system. Furthermore, as the content increases, the degree of crosslinking of the system gradually increases, and the viscous flow temperature and glass transition temperature also increase accordingly. However, excessively high nano-silica content can cause filler agglomeration, affecting the crosslinking density and thus the performance of the product.

[0067] Figure 4The tensile stress-strain curves show that the addition of nano-silica did not affect the mechanical properties of the products: the polyurethane composite elastomers in Examples 1-4 still exhibited higher performance compared to Comparative Example 1. In Example 5, excessive filler content led to agglomeration, resulting in a decrease in mechanical properties.

[0068] Figure 5 Atomic force microscopy (AFM) modulus images of the composite elastomer prepared in Example 1 are shown. Figure (a) shows the modulus of the material obtained after only one hot pressing followed by annealing, and Figure (b) shows the modulus of the material obtained after two hot pressings followed by annealing. The figures show that, for products with the same silica content (1 wt%), the product after one hot pressing-annealing treatment forms a dispersed hard phase region structure after microphase separation (acting as physical crosslinking points), while the product after two hot pressing-annealing treatment forms a continuous or connected hard phase region structure after microphase separation. This indicates that the two-stage hot pressing process is beneficial for optimizing the formation of the microphase separation structure.

[0069] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.

Claims

1. A method for preparing a polyurethane composite elastomer, characterized in that, Includes the following steps: (1) The polyurethane prepolymer is mixed with nanofillers and chain extenders to obtain the precursor; (2) The precursor obtained in step (1) is subjected to a first hot pressing and a second hot pressing. (3) The polyurethane composite elastomer is obtained after annealing. Wherein, the temperature T1 of the first hot pressing is lower than the temperature T2 of the second hot pressing; The temperature T1 of the first hot pressing is 80~100℃; the time of the first hot pressing is 8~10 min; and the pressure of the first hot pressing is 0.5~1 MPa. The temperature T2 of the secondary hot pressing is 180~220℃; the time of the secondary hot pressing is 10~20 min; and the pressure of the secondary hot pressing is 0.5~1 MPa. The nanofiller is selected from nano-silica.

2. The preparation method according to claim 1, characterized in that, The annealing temperature is 100~120℃.

3. The preparation method according to claim 1, characterized in that, The annealing time is 2-3 hours.

4. The preparation method according to claim 1, characterized in that, The polyurethane prepolymer is a diisocyanate-terminated polyether polyurethane prepolymer or a diisocyanate-terminated polyester polyurethane prepolymer, obtained by reacting polyether polyol or polyester polyol with diisocyanate.

5. The preparation method according to claim 4, characterized in that, The polyether polyol is polytetramethylene ether diol.

6. The preparation method according to claim 4, characterized in that, The polyester polyol is polybutylene adipate.

7. The preparation method according to claim 4, characterized in that, The diisocyanate is selected from at least one of toluene diisocyanate, diphenylmethane diisocyanate, and terephthalic diisocyanate.

8. The preparation method according to claim 4, characterized in that, The content of terminal isocyanate groups in the polyurethane prepolymer is 5-6 wt%.

9. The preparation method according to claim 1, characterized in that, The chain extender is dimethylthiotoluenediamine.

10. The preparation method according to claim 1, characterized in that, The particle size of the nanofiller is 40~60 nm.

11. The preparation method according to claim 1, characterized in that, The mass of the nanofiller is 0.5 to 3 wt% of the mass of the polyurethane prepolymer.

12. The preparation method according to claim 1, characterized in that, The molar ratio of terminal isocyanate groups to chain extender in the polyurethane prepolymer is 1:0.35~0.

45.

13. The polyurethane composite elastomer obtained by any of the preparation methods according to claims 1-12.

Citation Information

Patent Citations

  • Synthetic method of heat-resisting polyurethane elastomer

    CN104448197A

  • Medical polyurethane pancreaticojejunostomy device material and preparation method thereof

    CN104174072A